Farmers Perception About Salt Tolerant Wheat Varieties in Saline Areas of Gujarat - Nikam, Vinayak Ramesh; Chinchmalatpure, Anil; Kad, Sanjay (Indian Journal of Extension Education, 2016)
Salinity has been a major factor constraining agriculture in Gujarat. Use of salt tolerant varieties is considered as one of  economic and ecological approach to overcome this. Attempt was made to demonstrate potential of salt tolerant wheat  varieties (KRL 210 and KRL 19) in salt affected Vertisols of Bara tract area of Gujarat. Study was conducted with 53  farmers from Bharuch district of Gujarat. Data were collected using personal interview of the farmers using a well  structured interview schedule. Study found that in economic benefits, all farmers agreed that cultivation of salt tolerant  varieties in salt affected areas helped in increasing the income of the farmers. In terms of social benefits, about 76 per cent  farmers agreed that cultivation of salt tolerant varieties in saline areas helped in upliftment of small and marginal farmers  and achieving food security of the household. In terms of environmental benefits, 96 per cent farmers agreed that saline  land and moderate saline ground water could be effectively used for cultivation of salt tolerant varieties. For agronomic  practices majority of farmers agreed that salt tolerant varieties had more number of tillers (96%) and less lodging and  shattering tendency (92%). Under quality of output, all farmers agreed that eating quality of salt tolerant wheat varieties  was good. Thus farmers' response to salt tolerant wheat varieties was good, which helped them in increasing their income;  bringing their saline land under cultivation, securing household food security. However, there is need to create awareness  among farmers in salt affected areas of Gujarat about presence and potential of such varieties which would help in  increasing productivity and prosperity of these farmers.
Keywords: salinity; salt tolerant varieties; wheat; perception